2013
DOI: 10.1186/1755-7682-6-45
|View full text |Cite
|
Sign up to set email alerts
|

Motor development of infants exposed to maternal human immunodeficiency virus (HIV) but not infected

Abstract: BackgroundTo assess the motor development of infants exposed to maternal human immunodeficiency virus (HIV).MethodsThirty infants were assessed in the period from November 2009 to March 2010 at the AIDS Reference and Training Centre, in São Paulo, Brazil. The assessment instrument used in the research was the Alberta Infant Motor Scale (AIMS). All 30 infants used the antiretroviral drug properly for 42 consecutive days, in accordance with the protocol of the World Health Organization.ResultsOut of the total nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
0
7
0
9
Order By: Relevance
“…However, while scientific production has been increasingin Brazil, it would significantly increase with the proper training of health professionals who work with management projects research. 16,18 According to the BLS course of the American Heart Association (2010), individuals are considered qualified when scores of 84% are obtained in a questionnaire similar to that in Annex 1. However, of the 664 subjects who completed the questionnaire on BLS, just one achieved a scoregreater than or equal to 84% and the others had lowerresults in this American Heart Association's indicator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while scientific production has been increasingin Brazil, it would significantly increase with the proper training of health professionals who work with management projects research. 16,18 According to the BLS course of the American Heart Association (2010), individuals are considered qualified when scores of 84% are obtained in a questionnaire similar to that in Annex 1. However, of the 664 subjects who completed the questionnaire on BLS, just one achieved a scoregreater than or equal to 84% and the others had lowerresults in this American Heart Association's indicator.…”
Section: Discussionmentioning
confidence: 99%
“…17. The basic life support consists of: a) airway opening intubation, orotracheal ventilation, thoracic compressions, vascular access, use of adrenaline b chest compressions, airway, ventilation, defibrillation (AED) c) chest compressions, tracheal intubation, ventilation, defibrillation (AED), vascular access d) vascular access, opening of airway, ventilation, chest compressions, adrenaline, manual defibrillation 18. With respect to ventilation of the patient in BLS, tick the correct alternative: a) must be asyn chronous with the compressions during CPR b) in the case of having initially only a respiratory failure, we should ventilate the child 30 time sper minute c) each ventilation should last about 5 seconds and we must promote a large thoracic expand ability…”
mentioning
confidence: 99%
“…The AIMS evaluates the weight bearing, posture and antigravity movements in the gross motor development in infants up to 18 months of age. Previous studies showed that this instrument can be applied to samples with various clinical characteristics 7,22 , besides showing an interobserver agreement of > 0.96 and test-retest reliability ranging from 0.86 to 0.99 23 . Concurrent validity (8-13 months) with other standard motor assessments (such as Bayley Scales) ranges from 0.84 to 0.99 24,25 .…”
Section: Methodsmentioning
confidence: 91%
“…Another distinguishing feature of this study is to use both a screening instrument (DDST-II) and a test and assessment scale of infant motor development (TIMP and AIMS) in the first year of the infant's life. The literature suggests that the a p p l i c a t i o n o f s t a n d a r d i z e d a n d r e l i a b l e assessment instruments minimizes the chance of misdiagnosis and offers the examiner the tools to monitor the development of preterm infant in the long term [16][17][18][19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…e a executiva (atenção sustentada, planejamento da ação e etc.) podem estar comprometidas em indivíduos infectados (HERRERO et al, 2013). Em crianças, o efeito do HIV no SNC imaturo é mais prejudicial e os comprometimentos neurológicos ocorrem em 15% a 40% de todos os casos de infecção (HUTCHINGS; POTTERTON, 2013;CAPELO et al, 2016), destacando que qualquer interrupção do processo de crescimento e desenvolvimento do SNC pode resultar em atrasos do desenvolvimento motor, cognitivo, da linguagem e comportamental, que podem se tornar mais significativos com o passar dos anos, pois muitas vezes aparecem na idade escolar (BLANCHETTE et al, 2001).…”
Section: Introductionunclassified